A Biomarker of Developmental Health Is Predictive of Cross-National and Cross-Regional Differences in Academic Achievement - David C. Geary; Lewis G. Halsey (Intelligence & Cognitive Abilities, 2026)
Academic competencies at the end of schooling influence the life trajectories of individuals and the economic functioning of populations. Nations, and regions within them, differ dramatically in these outcomes, but the sources of this variation are debated. Our goal was to test the hypothesis that these relations are related in part to national and regional differences in developmental health. We propose that the magnitude of the difference between the sexes in adult height is a sensitive measure of developmental health and show that national variation in height sexual dimorphism explains substantial amounts ( d s ~ 0.2 to 0.3) of cross-national variation in academic achievement as measured by international achievement data provided by the World Bank. The effects were most pronounced for dimorphisms up to 1.08 (men being 8 percent taller than women), with gains above this having little effect. The within-nation effects partially replicate the cross-national pattern for achievement and show it extends to general cognitive ability but there were discrepant results for two nations that remain to be explained. The findings have implications for the development of health-related interventions that could improve the ability of at-risk children to gain from educational experiences, especially in developing nations.